The radiographic assessment of lung edema score of lung edema severity correlates with inflammatory parameters in patients with coronavirus disease 2019—Potential new admission biomarkers to predict coronavirus disease 2019 worsening - Marques, Patrice; Fernandez-Presa, Lucia; Carretero, Aitor; Gómez-Cabrera, Maria-Carmen; Viña, José; Signes-Costa, Jaime; Sanz, Maria-Jesus (Frontiers in Medicine, 2022)
Background: Coronavirus disease 2019 (COVID-19) has placed enormous pressure on intensive care units (ICUs) and on healthcare systems in general. A deeper understanding of the pathophysiology of the most severe forms of COVID-19 would help guide the development of more effective interventions. Herein, we characterized the inflammatory state of patients with COVID-19 of varying degrees of severity to identify admission biomarkers predicting COVID-19 worsening. Design: Admission blood samples were obtained from 78 patients with COVID-19. Radiographic assessment of lung edema (RALE) scoring was calculated by imaging. Platelet and leukocyte counts were measured by flow cytometry, and plasma levels of C-reactive protein were assessed by immunoturbidimetry, and IL-8/CXCL8, IL-10, TNFα, IFNγ and MCP-1/CCL2 levels by ELISA. Results: The RALE score correlated with several admission hemogram (platelets, neutrophils and lymphocytes) and inflammatory (IL-8/CXCL8, MCP-1/CCL2, IL-10 and C-reactive protein) parameters. COVID-19 worsening, based on the need for oxygen (Δoxygen supply) during hospitalization, correlated negatively with admission lymphocyte counts but positively with neutrophil-to-lymphocyte ratio and with plasma levels of the inflammatory parameters correlating with RALE score. Conclusion: Our data indicate a correlation between the RALE score and Δoxygen supply and admission inflammatory status. The identification of a panel of biomarkers that reflect COVID severity might be useful to predict disease worsening during hospitalization, and to guide clinical management of COVID-19-related complications. Finally, therapies targeting IL-8/CXCL8- or IL-10 activity may offer therapeutic approaches in COVID-19 treatment.